Is Providence Credible Today? - Robinson, Norman H. G. (Scottish journal of theology, 1977)
Much of the recent debate about religion has concerned itself either with the bare existence of God or with the fact of Jesus Christ, and has not directly brought into the discussion the question of providence and the allied topic of prayer. It is as if the whole area were so problematic that thought has tended to polarise around these two points, God in heaven and Jesus of Nazareth in history, and as a result has virtually by-passed this subject, although one would have thought that it lay very close to the living core of religion. Yet this neglect is not without precedent in the past. It is worth recalling that Immanuel Kant, although he was profoundly critical of the traditional ways in which the existence of God had been proved and the foundation of religion laid, none the less believed himself that there is a legitimate foundation for religious belief in man's consciousness of value, in his awareness of what Kant called the categorical imperative; and this more practical, this less severely theoretical approach to the reality of religion, may well be regarded as an important pointer towards the truth. None the less the fact remains that Kant himself held that ‘the purpose of prayer can only be to induce in us a moral disposition. … To wish to converse with God is absurd: we cannot talk to one we cannot intuit; and as we cannot intuit God, but can only believe in him, we cannot converse with him.’